Identifikasi Tahapan dan Faktor-Faktor Sosial Pembangunan Hutan Rakyat di Sekitar Kawasan Hutan Lindung - Cecep Handoko; C. Yudilastiantoro; Agus Sukito (Jurnal Penelitian Kehutanan Wallacea, 2012)
Development of private forests was thought to have good impact on the security of protected forest. The development could increase the ability of farmers in managing degraded lands, especially on private lands around the protected forest, so the disruption to the forest is reduced. The study was conducted in Sajang Village, East Lombok District and Bentek Hinterland, North Lombok District. Social factors were collected, such as education of farmers, forest ownership, local perceptions, and perception farmers towards forests, local institutions and the characteristics of the management of protected forest. Interview was conducted on 50 respondents for each location. Analysis data was done through correlation test, factor selection, and regression test. At 95% confidence level, was elected four factors associated with the ownership of private forests by farmers, namely: age of farmers, local institutional goals, pressure to local institutions and knowledge of farmers about the benefits of protected forest. Based on the four factors, the changes in the activity of local communities from depending on forest resources to building private forest was occured gradually over a long time, but it could be accelerated by increasing the independence of local institutions, and by the efforts to increase understanding of farmers in the benefits of protected forest.